The Diffusion of Stock Ownership in the United States - Means, Gardiner C. (Quarterly Journal of Economics, 1930)
Growth in number of book stockholders in recent years, 561. — More rapid growth in immediate post-war period, 566. — Customer and employee sales important only after 1920, 567. — Examination of income-tax data for possible shift in ownership, 570. — Large shift in ownership from rich to less rich apparent between 1916 and 1921, none thereafter, 574. — Check on validity of figures by examination of methods of manipulation, 575; by examination of income-tax data, particularly for tax evasion, 576; by discussion of possible explanations of shift, 585; by the evidence of growth in number of book stockholders, 591. — Conclusion, 591. — Statistical Appendix, Tables I–VIII, 593.